2023
DOI: 10.1002/ijgo.14785
|View full text |Cite
|
Sign up to set email alerts
|

Unintended lower‐segment hysterotomy extension at cesarean delivery and the risk for uterine rupture during a subsequent trial of labor

Abstract: ObjectiveTo evaluate the association between unintended uterine extension in cesarean delivery and uterine scar disruption (rupture or dehiscence) at the subsequent trial of labor after cesarean delivery (TOLAC).MethodsThis is a multicenter retrospective cohort study (2005–2021). Parturients with a singleton pregnancy who had unintended lower‐segment uterine extension during the primary cesarean delivery (excluding T and J vertical extensions) were compared with patients who did not have an unintended uterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The details of the study have previously been reported. 21 For this analysis, patients with singleton pregnancies and one prior low-segment cesarean delivery who attempted a first trial of labor between 24 and 42 weeks of pregnancy were included. Several exclusion criteria were applied: patients who did not have both the primary cesarean and subsequent TOLAC at the study hospitals,; patients with elective repeat cesarean delivery or prelabor indications for cesarean; and those with previous multiple cesareans, multifetal gestation, fetal major malformation, out-of-hospital deliveries, and a malformed uterus.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The details of the study have previously been reported. 21 For this analysis, patients with singleton pregnancies and one prior low-segment cesarean delivery who attempted a first trial of labor between 24 and 42 weeks of pregnancy were included. Several exclusion criteria were applied: patients who did not have both the primary cesarean and subsequent TOLAC at the study hospitals,; patients with elective repeat cesarean delivery or prelabor indications for cesarean; and those with previous multiple cesareans, multifetal gestation, fetal major malformation, out-of-hospital deliveries, and a malformed uterus.…”
Section: Inclusion Criteriamentioning
confidence: 99%